IMPLEMENTASI KONSEP PARIWISATA BERBASIS MASYARAKAT DALAM PENGELOLAAN PANTAI KEDONGANAN - Anom Hery Suasapha (Magister Tourism Study, Faculty of Tourism, Udayana University, 2016)
Kedonganan beach is a tourist destination located in KedongananVillage, South Kuta, Bali, known for its scenic beauty and theculinary activity. The beach was a fisherman village, until tourismdeveloped in the area during 1995. The tourism developmentwas not a carefully planned, resulted in many negative effectson the area and also to the community. A correction plan was developed based on Community Based Tourism (CBT) concept, and has been implemented since 2006. This article discusses the implementation process of community based tourism (CBT) in Kedonganan Beach. The enabling factors and the barrier of the implementation are also discussed, and the model of CBT implemented in the area are developed and discussed. The analysis result shows that implementation of CBT concept in the management of Kedonganan has been done in two steps. Thesesteps were devided into smaller steps, in which four CBT principleswere implemented. Local inisiative, support from Badung Regency Government and social capital were some of the factors that enables the implementation of CBT concept in Kedonganan Beach, while rejection from some of the community member and different perception of the community toward the lagal status of the land were the barriers of the implementation.